The patient perspective on remote monitoring of implantable cardiac devices - Hillmann, Henrike A. K.; Hansen, Claudius; Przibille, Oliver; Duncker, David (Frontiers in Cardiovascular Medicine, 2023)
Aims Remote monitoring for patients with cardiac implantable electronic devices (CIEDs) is well established in clinical routine and recommended by current guidelines. Nevertheless, data regarding patients’ perceptions are limited. Therefore, this study aims to analyze the patient perspectives on the remote monitoring of cardiac devices in Germany. Methods and results Patients with CIEDs and remote monitoring of all current manufacturers from three German centers were asked to participate. The questionnaire consisted of 37 questions regarding the patients’ individual use and perspectives on remote monitoring. Survey participation was anonymous and on a voluntary basis. A total of 617 patients (71.6% men) participated. Most patients reported feeling well informed (69.3%) and reported having unchanged or improved coping (98.8%) since the start of remote monitoring. At least 39.7% of patients experienced technical problems regarding the transmitter, whereas most patients (60.3%) reported that they never noted technical issues. Older patients had significantly less interest than younger patients in using their own smartphones for data transfer (p < 0.001). Conclusion Patients with remote follow-up of CIED reported that they felt well informed about the remote monitoring approach. Remote monitoring can support coping with their disease. With remote monitoring, patients experienced a prolongation of intervals of in-person follow-up visits, and especially younger patients would appreciate smartphone-based data transfer of their CIEDs.